2020
DOI: 10.21307/jelpp-2020-005
|View full text |Cite
|
Sign up to set email alerts
|

An evolution in distributed educational leadership: From sole leader to co-principalship

Abstract: This paper traverses changes in perceptions of the school principal's role, from sole to distributed leadership practices. A brief commentary on selected New Zealand literature is followed by a case study of a secondary co-principalship that identifies adaptive strategies and success factors in this joint role. The potentiality of the national Leadership Strategy (2018) and Educational Leadership Capability Framework (2018) to impact these distributed features will then be explored. The paper concludes with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…While the first two success factor areas consider how personal qualities influence the nature of successful leaders' behaviours or practices, attention has also been drawn to the bicultural nature of Aotearoa New Zealand and the importance of culturally relevant and situational leadership strategies outlining how successful practices are enacted in a context with cultural responsiveness. In combination with the situational and cultural demands related to their contextual circumstances, some findings show that successful principals acknowledged the need to strengthen culturally responsive and relational pedagogies, advance an inclusive school culture and a culture of success for all, especially for indigenous Māori students, and reframe the curriculum to address local needs [10,12]. One primary case of a principal in a Māori girls' college highlighted the need for new principals to re-assess the existing school context before implementing any changes.…”
Section: Culturally Relevant and Situational Leadership Practices And...mentioning
confidence: 99%
See 1 more Smart Citation
“…While the first two success factor areas consider how personal qualities influence the nature of successful leaders' behaviours or practices, attention has also been drawn to the bicultural nature of Aotearoa New Zealand and the importance of culturally relevant and situational leadership strategies outlining how successful practices are enacted in a context with cultural responsiveness. In combination with the situational and cultural demands related to their contextual circumstances, some findings show that successful principals acknowledged the need to strengthen culturally responsive and relational pedagogies, advance an inclusive school culture and a culture of success for all, especially for indigenous Māori students, and reframe the curriculum to address local needs [10,12]. One primary case of a principal in a Māori girls' college highlighted the need for new principals to re-assess the existing school context before implementing any changes.…”
Section: Culturally Relevant and Situational Leadership Practices And...mentioning
confidence: 99%
“…Successful principals in these cases embraced shared decision-making and leadership approaches that offered greater opportunities for capacity building through distributed leadership roles and succession planning. For example, Notman reports on a case study of two secondary co-principals that identified adaptive strategies and success factors in a joint leadership role [12]. Despite the challenges in a joint senior leadership position, both co-principals had been successful at the school because the clarity of their vision and values informed their day-to-day practices and behaviours and were considered as some of the core success factors.…”
Section: Culturally Relevant and Situational Leadership Practices And...mentioning
confidence: 99%
“…The results of improving this educational change are interpreted at both the individual and the group level through the cooperation of the two principals. Moreover, when interest moves away from the achievements of the principal's school unit, attention can be turned to important issues such as effective and efficient teaching and learning, mentoring and communication (Court, 2003;Notman, 2020).…”
Section: Two Principals Together: Separating the Pedagogical And Admi...mentioning
confidence: 99%